Microbial Profile of Imported Carcass under Chilled Storage - Hussein, Esraa F.; Meawad Ahmed, Ali; Elghayaty, Hanan A.; Mohamed Shaheen, Heba (Journal of Advanced Veterinary Research, 2022)
Bacterial contamination has been proven to be common in a variety of foods, especially meats. For this reason, this study was conducted to evaluate the bacteriological quality of imported chilled meat traded in Port-Said markets where 64 random samples of chilled meats represented by 28 imported chilled beef meat samples from lots arrived at Port-Said port (un-marketed) and 36 imported chilled beef meat samples collected from retailed markets at Port-Said governorate (marketed). Samples were analyzed for their total aerobic count., Enterobacteriaceae count, E. coli, total staphylococcus, and S. aureus counts and detection of salmonellae. The total bacterial count recorded an average of 10.73x104 and 2.5x106 in un-marketed and marketed chilled meat respectively. The results showed that 18 out of 64 meat samples were positive for Enterobacteriaceae and 6 samples out of them were unaccepted for human consumption. The incidence of E. coli was in 6 samples from the examined chilled samples, and the 6 were unaccepted. For staphylococcus, there were 24 positive samples, and 13 out of them were unaccepted and for S. aureus, 4 samples out of 64 samples were positive and 4 samples were unaccepted for consumption. Two samples out of 64 were positive for salmonella and considered unfit for human consumption. The obtained results confirmed the poor bacteriological quality of some imported chilled meat that is marketed in Port-Said retailed markets which is related to unhygienic transportation methods until reach the retailed markets.